The Use of Whatsapp Application in Teaching Reading Comprehension - Dian Arianti (English Education Department Slamet Riyadi University Surakarta, 2020)
The aims of the research was to describe the implementation of whatsapp application in teaching reading comprehension, to know the problems faced by the students in teaching reading comprehension by whatsapp application and to know the problems faced by the teacher in teaching reading comprehension by whatsapp application. This research used Qualitative descriptive research. The subject of this research was class VIIIF of SMPN 18 Surakarta in Academic Year 2019/2020. To collect the data, the researcher used questionnaires and interview with teacher and students. After collecting the data the researcher analyzed the data by using qualitative anaylsis data. The qualitative anaylsis data consisted of data collection, data reduction, data display and data verification. The result of this research showed that the teacher explained the material before giving the assignments through whatsapp. During teaching learning process the teacher did not give the punishment when the students did not submit the assignments. There were some problems faced by students such as there was bad internet connections and the students were lack of understanding the material. While there were also some problems faced by the teacher such as there was bad internet connections and the teacher could not monitor students directly. Keywords: The use, teaching reading, whatsapp application, Reading comprehension